Model of Improving Business Success through Entrepreneurship Competency and Business Environment Mediated by Competitiveness in the Garment Industry in West Java - Syahyono, S. (Budapest International Research and Critics University, 2021)
This study aims to analyze the effect of entrepreneurial competence and business environment on business success mediated by competitiveness. The research method uses descriptive-quantitative, with the type of descriptive-verificative survey research. The sampling technique used is proportional random sampling, so a sample representation of 254 respondents is obtained. Descriptive analysis and verification analysis were used for data processing. The results showed that all constructs were included in the low category (achievement below 50%). And the power construct variance (DS) can be explained by the entrepreneurial competence (KK) and the environment (LB) of 65.1% of the business; the remaining 9% is influenced by other factors not examined. Based on the study results, it can be said that Entrepreneurship and Environmental Competencies positively affect competitiveness. Likewise, both directly and through competitiveness, Entrepreneurial Competence and the business environment positively impact business success. And Power has a positive effect on business success. Low competitiveness resulted in the achievement of the clothing industry in West Java, and low competence and a less conducive environment also participated. Especially during a pandemic like now.